2021
DOI: 10.1002/ajmg.a.62384
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the clinical phenotype of GALE deficiency

Abstract: Congenital disorders of glycosylation are a group of rare monogenic inborn errors of metabolism caused by defective glycoprotein and glycolipid glycan synthesis and attachment. Here, we present a patient with galactose epimerase deficiency, also known as GALE deficiency, accompanied by pancytopenia and immune dysregulation. She was first identified by an abnormal newborn screen for galactosemia with subsequent genetic evaluation due to pancytopenia and immune dysregulation.The evaluation ultimately revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that proper glycosylation is crucial to normal hemopoiesis, in particular to megakaryocyte and platelet development; defects in genes regulating sugar metabolism and glycosylation can be associated with bone marrow failure [7,8]. Moreover, in an animal model of galactosemia, newborn GALT gene-trapped mice presented manifestations of oxidative stress in red blood cells (altered glutathione/oxidized glutathione ratio), a fact to which our patient's anemia could be also attributed [2].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies have shown that proper glycosylation is crucial to normal hemopoiesis, in particular to megakaryocyte and platelet development; defects in genes regulating sugar metabolism and glycosylation can be associated with bone marrow failure [7,8]. Moreover, in an animal model of galactosemia, newborn GALT gene-trapped mice presented manifestations of oxidative stress in red blood cells (altered glutathione/oxidized glutathione ratio), a fact to which our patient's anemia could be also attributed [2].…”
Section: Discussionmentioning
confidence: 66%
“…This is a case of galactosemia in a neonate who presented with both acute liver failure and cytopenias. Neonatal acute liver failure has been well described in the literature in patients with galactosemia; on the contrary, cytopenias have only rarely been reported either in the context of secondary hemophagocytic lymphohistiocytosis in galactosemia [3], similar to other metabolic disorders [5,6] or terms of inherited/chronic thrombocytopenia or pancytopenia associated with mutation of UDP-galactose-4epimerase [7,8]. Hemophagocytic lymphohistiocytosis was not confirmed in our patient because only three out of the eight diagnostic criteria [4] were fulfilled (cytopenia, low fibrinogen, and elevated ferritin).…”
Section: Discussionmentioning
confidence: 99%
“…Galactosemia includes a rare group of hereditary disorders of galactose metabolism. To date, four types have been described, each affecting a different step in the main route of galactose disposal: type I, resulting from GALT deficiency; type II, resulting from GALK1 deficiency; type III, resulting from GALE deficiency; and the recently described type IV galactosemia, resulting from GALM deficiency [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Partial transferase deficiency is more common than classic galactosemia, is asymptomatic, and is diagnosed by screening the newborn based on a determination of moderately increased blood galactose and/or low transferase activity. The condition should be taken into consideration for the newborn who is underweight or has any of the above signs and symptoms [ 17 , 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most GALE deficiencies consist of the “peripheral” type, in which the deficiency is restricted to red and white cells, and has virtually no symptoms. GALE deficiency, however, is considered a continuum disorder rather than a binary condition [ 19 ] and it has also been associated with thrombocytopenia [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%